1986
DOI: 10.1037/0012-1649.22.6.766
|View full text |Cite
|
Sign up to set email alerts
|

Preschool temperament and performance on achievement tests.

Abstract: All APA members (Fellows, Members, and Associates) receive -as part of their annual dues -subscriptions to the American Psychologist, the APA Monitor, and Psychology Today. High School Teacher and Student Affiliates receive subscriptions to the APA Monitor and Psychology Today, and they can subscribe to the American Psychologist at a significantly reduced rate.In addition, all members and affiliates are eligible for savings of up to 50% on other APA journals, as well as significant discounts on subscriptions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…According to findings from some studies, children with higher activity levels had poorer academic achievement (Martin & Holbrook, 1985;Martin et al, 1988;Palisin, 1986), while other evidence suggests that higher temperamental activity may be related to academic success (DiLalla et al, 1990;Molfese et al, in press). We found that children with higher levels of activity had better academic achievement than less active children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to findings from some studies, children with higher activity levels had poorer academic achievement (Martin & Holbrook, 1985;Martin et al, 1988;Palisin, 1986), while other evidence suggests that higher temperamental activity may be related to academic success (DiLalla et al, 1990;Molfese et al, in press). We found that children with higher levels of activity had better academic achievement than less active children.…”
Section: Discussionmentioning
confidence: 99%
“…Findings regarding the relationship between activity level and academic achievement may be related to the context in which activity is assessed. On the one hand, concurrent and longitudinal studies examining activity and achievement in preschool and elementary grades have suggested that higher activity is detrimental to children's academic success (Martin et al, 1988;Martin & Holbrook, 1985;Palisin, 1986). For example, Martin and colleagues (i.e., Martin & Holbrook, 1985;Martin et al, 1988) used teacher ratings of children's gross motor activity in the classroom to predict academic achievement in elementary school.…”
Section: Contributions Of Temperament To Academic Achievementmentioning
confidence: 99%
“…Further, an overlap between the two constructs has been empirically noted (Andersson & Sommerfelt, 1999;Bauer, Burch, & Kleinknecht, 2002;Halpern, Garcia Coll, Meyer, & Bendersky, 2001;Kubicek, Emde, & Schmitz, 2001;Lewis, 1993;Martin & Holbrook, 1985;Matheny, 1989;Mevarech, 1985;Miceli, Whitman, Borkowski, Braungart-Rieker, & Mitchell, 1998;Newman, Noel, Chen, & Matsopoulos, 1998;Palisin, 1986). Rothbart and Bates (1998) defined temperament as biologically based individual differences in emotional, motor, and attentional reactivity and self-regulation.…”
Section: Temperamentmentioning
confidence: 99%
“…Many of the researchers examining temperament in young children have examined relations between temperament and adjustment in various structured environments as schools [5]. The child who is better to adjust to his/her environment is more likely to work his/her potential in academic achievement.…”
Section: Effect Of Temperament On Academic Performancementioning
confidence: 99%